2017
DOI: 10.4103/ijpvm.ijpvm_179_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interleukin-33 serum levels in asthmatic patients with a control group and relation with the severity of the disease

Abstract: Background:The relation between interleukin-33 (IL-33) and asthma is not precisely known yet. The present study set to compare the serum level of IL-33 in patients with asthma and controls and study the relation with the severity of disease.Methods:The serum level of IL-33 and total IgE in 89 asthmatic patients and 57 controls were analyzed. The association of levels of IL-33 with the severity of disease, levels of total IgE, measures of spirometry (forced expiratory volume in 1 s [FEV1]), age, sex, presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous studies have shown low but significantly elevated levels of serum IL-33 in patients with seasonal influenza A [30]. In contrast, higher levels of IL-33 were measured in asthmatic patients, and these levels increased with the severity of the disease, suggesting that elevated IL-33 is responsible for the exacerbation of asthmatic diseases [31]. IL-33 also regulates other allergic diseases, including atopic dermatitis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown low but significantly elevated levels of serum IL-33 in patients with seasonal influenza A [30]. In contrast, higher levels of IL-33 were measured in asthmatic patients, and these levels increased with the severity of the disease, suggesting that elevated IL-33 is responsible for the exacerbation of asthmatic diseases [31]. IL-33 also regulates other allergic diseases, including atopic dermatitis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that IL-33 production is an attempt to limit inflammation accompanying relapse in schizophrenia. However, direct pathogenic effect cannot be excluded as ST2 dependent Th2 pathology reported to be common denominator in asthma and schizophrenia ( 57 ). Considering that sST2 binds directly to IL-33 or acts as a decoy receptor when competing with membrane bound ST2 [reviewed in 28 ], higher systemic level of sST2 in FEP and SC patients in relapse as well as negative correlation of this molecule with N subscore in acute psychosis may represent compensatory mechanism in suppressing IL-33-dependent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IL-33 is closely associated to asthma, since it is increased in asthmatic patients ( 154 ) and was shown to potentiate airway hyper-reactivity ( 136 ). Notably, IL-33 was shown to directly impair T REG cell function during antigen-driven type 2 airway hyper-reactivity ( 131 ) and enhance T H 2 differentiation through enhanced OX40 ligand interaction ( 155 ).…”
Section: Regulatory T Cellsmentioning
confidence: 99%